Russia’s War Crimes: Justice and Responsibility - Khmilevska, Polina (Polityka i Społeczeństwo, 2023)
The world has been shaken by the new stage ofbloody and unfair war that Russia started against Ukraine on February 24, 2022. This time the full-scale invasion resulted in horrific consequences: huge destructions, numerous war crimes and civil losses. However, everything what Kremlin and its army are doing is nothing new in the historical perspective and the world has already tolerated many crimes of Russia’s regime. In the era of digitalization Russia’s war against Ukraine might be the most documented war ever, which gives a great chance for justice. That is why, it is in interest of whole international community to contribute to Ukraine’s victory and then documentation, investigation and prosecution of all crimes of Russians in Ukraine. That is crucial to stop the chain ofimpunity and to eventually downfall of Putin’s regime and Russia’s imperialism.